Performing Endoscopic Retrograde Cholagiopancreatpgraphy and Endoscopic Ultrasound for Management of Malignant Bile Duct Obstruction in a Patient With a Situs Inversus Totalis. Issue 12 (7th December 2020) - Coronel, Martin; Lanke, Gandhi; Cambell, Donald; Coronel, Emmanuel; Tzeng, Ching-Wei D.; Foo, Wai; Lee, Jeffrey H.
ABSTRACT: Situs inversus totalis (SIT) is a rare anomaly characterized by the transposition of organs. We present a case of a 67-year-old White woman with a history of SIT, who presented with fatigue, jaundice, and abnormal liver enzymes. Endoscopic ultrasound demonstrated a solid lesion at the distal common bile duct (CBD). Subsequent endoscopic retrograde cholangiopancreatography displayed severe stenosis in the CBD. A plastic stent was placed into the CBD, resulting in successful biliary decompression. Biliary brushings and biopsy showed atypical cells, suspicious for carcinoma. Ensuing pancreaticoduodenectomy confirmed cholangiocarcinoma. Although challenging, endoscopic ultrasound and endoscopic retrograde cholangiopancreatography in SIT can be successfully performed in preoperative evaluation for possible pancreaticobiliary cancers.